Pembangunan Modul Pembelajaran Bahasa Inggris Menggunakan Grammar Translation Method Berbasis Android - Noviani Kurnia Ambarwati; Rita Wiryasaputra; Shinta Puspasari (Ultimatics : Jurnal Teknik Informatika, 2016)
English has become the international language now used in almost all areas of global life and connect to transfer knowledge to the whole world, for the mastery of the English language allows a person to expand interaction in the international world. To help in learning English to primary school students, especially in class 3-5 primary school will be built learning module applications. In order to teach English well, better know the methods used in the process of learning English in primary school is the grammar translation method (GTM), which is a method of teaching grammar to the main characteristics focusing on translation (translation) and to memorize verb forms. This application is intended as an alternative to learning to enhance students’ understanding of the material about the translation and pronunciation of English interactive fun, the application is built using the Android operating system. Index Terms— Android, English, Elementary students, Grammar Traslations Method, Learning Module.